Simulation of Drag Reducer Polymer (DRP) for Single and Annular Two Phase Flow in Horizontal Pipe - Dianita, Cindy; Saputra, Asep Handaya; Khairunissa, Puteri Amelia (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2018)
Drag reducing polymers (DRP) is one of drag reducer types that is widely used in industry as an additive to improve fluid flow efficiency in pipes. This study is conducted to analyze the parameters that influence the efficiency of DRP through developing equation model, and to see the phenomenon of drag reduction that occurs in fluid flow through computational fluid dynamic (CFD) simulation. The data used are obtained from experiments by Vancko (1997) for a single phase flow of water. As for two-phase annular flow, four experiments data are used namely by Vancko (1997), Al-Sarkhi and Hanratty (2001a,b) and Fernandes et al. (2004). Parameters such as fluid velocity and pipe diameter are analyzed based on the model equations proposed in this study. The final single phase flow equation model as the output of this study gives a value for onset drag reduction i.e 4.00 with an error up to 18%. While the proposed annular flow equation with and without drag reduction effect is only suitable when the condition of fluid film distribution is uniform and symmetrical with the error around 20%, i.e. for smaller diameter pipes. The CFD simulation results shows a change in the fluid velocity profile; becoming more parabolic, indicating an increase in the mean fluid velocity up to 0.43%, as the effect of DRP.